Implementing Stylistics in IELTS Writing Preparation Focusing on Noun Phrases - Erina Andriani; Stella Noviani; Barli Bram (Journal of Foreign Language Teaching and Learning, 2021)
In the IELTS writing preparation class, the teacher can facilitate the students by integrating the stylistic approach in building writing students’ style. Not only achieving the primary goals in English proficiency by focusing on the writing style, but students can also comfortably share their ideas in their style. The paper examined the stylistics integrated material in IELTS writing through noun phrase construction. This study employed a qualitative method and a descriptive design. The data were collected using structured observation sheets as the instrument and were analyzed stylistically. Writing materials and the writing results of 12 students at an English course were collected. Results showed that stylistics was used in phrase complexity and ambiguity as a part of writing strategies. It was supported by the three dominant types of noun phrases produced by the students in their writing: determiner + head, determiner + pre-modifier + head, and pre-modifier + head, as the evidence of the implementation of integrated material in IELTS writing. For the noun phrase uses, the students could vary the noun phrases in their complexity, function, and type in their tests, though the variations in each of those aspects were still low. Implications of the results are stylistics could be implemented in language learning-teaching activities in general. It could encourage students to develop their writing style for self-expression and more explicit writing products.